Contribution to the knowledge of Chinese Gryllacrididae (Orthoptera) XV: Two new species of Larnaca (Larnaca) from Yunnan Province - Zhang, Qianwen; Zhang, Bin; Bian, Xun (Zootaxa, 2023)
Two new species of Larnaca Walker, 1869, Larnaca (Larnaca) longispina sp. nov. (Chinese name: 长刺原蟋螽) and Larnaca (Larnaca) nigrimacula sp. nov. (Chinese name: 黑斑原蟋螽), are described from Yunnan Province, China based on new material deposited in Guangxi Normal University. The two new species are placed Larnaca (Larnaca) Walker, 1869 and compared to the corresponding closely related species. The male of Larnaca (Larnaca) longispina sp. nov. and both sexes of Larnaca (Larnaca) nigrimacula sp. nov. are illustrated.